Historical Paradigm and Polemics In The Right To Freedom Of Speech In Public Space In The 21st Century - Musyaffak, Wafiyuddin; Pandin, Moses Glorino Rumambo (Universitas Negeri Surabaya, 2021)
The right to freedom of speech is a natural right owned by every human being born on earth. However, with the development of the times, freedom of speech has experienced many steep paths in practice. This study aims to provide insight into how the historical and polemic paradigms are faced in freedom of speech in the 21st-century public sphere, especially in its development and practice. The method used in this research is to qualitative research methods with the approaches literature review of the literature resources during the last three years, which was in 2019-2021. The result of this study is to provide insight into the historical and polemic paradigms that occur in the right to free speech in the 21st century. The conclusion is that freedom of speech is very important but we must remember that our freedom is limited by the freedom of others.The right to freedom of speech is a natural right owned by every human being born on earth. However, with the development of the times, freedom or freedom of speech has experienced many steep paths in practice. This study aims to provide insight into how the historical and polemic paradigms are faced in freedom of speech in the 21st-century public sphere, especially in its development and practice. The method used in this research is to qualitative research methods with the approaches literature review of the literature resources during the last three years, which was in 2019-2021. The result of this study is to provide insight into the historical and polemic paradigms that occur in the right to free speech in the 21st century. The conclusion is that freedom of speech is very important but we must remember that our freedom is limited by the freedom of others.